Relationship Between Learning Styles and Academic Performance in Yarsi University Medical Student - Marylin Christio; Zwasta Pribadi Mahardika; Endy Istiwara (Junior Medical Journal, 2023)
Methods of medical education in Indonesia continue to experience development in line with the development of medical science and practice which has made many advances in pursuing public health. Medical education students are expected to be adaptive in achieving predetermined medical competencies. The results of the study stated that there were several factors that influenced the low achievement of students including learning strategies, learning motivation, psychological conditions, family, and health problems. Research by Jafari et al. states that there is a significant relationship between learning styles and student academic achievement.Learning styles that are consistent and in accordance with student character can improve academic achievement. The things that cause differences in learning styles include culture, ways of education, and the teaching and learning process in each institution. The data collected in this study there are 2 types of data, namely primary and secondary. Primary data collected with the VARK questionnaire instrument to assess learning styles. The secondary data collected was in the form of GPA of Yarsi University Faculty of Medicine students for the 2022/2023 academic year. The total number of respondents in this study was 240 consisting of batches of 2019, 2020, 2021, and 2022. Students of the Faculty of Medicine, Yarsi University, batches of 2019, 2020, 2021, and 2022 with a total of 240 respondents, 24 of whom had a Visual learning style (10%) , Auditory 26 (11%), Reading 118 (49%), Kinesthetic 22 (9%), and Multimodal 50 (21%). The relationship between learning styles and the Grade Point Average (GPA) has a weak correlation.